The epistemic lightness of truth : deflationism and its logic - Cieslinski, Cezary (New York : Cambridge university press, 2017)
This book analyses and defends the deflationist claim that there is nothing deep about our notion of truth.
Includes bibliographical references and index.
Keywords: Truth; PHILOSOPHY - Epistemology